Modeling with Limited Data : Estimating Potential Growth in Cambodia - Rungcharoenkitkul, Phurichai (IMF Working Papers; Working Paper ;, 2012)
This paper proposes a framework to analyze long-term potential growth that combines a simple quantitative model with an investigative approach of 'growth diagnostics'. The framework is used to forecast potential growth for Cambodia, and to conduct simulations about the main drivers of growth in that country. The main result is that Cambodia compares less favorably against other lower-income Asian economies in terms of its investment rate, which in turn is constrained by the poor quality of its infrastructure. Bridging this gap can lift Cambodia's potential growth by more than one percentage point.